The design of the “archive wall” at Aphrodisias - Kokkinia, Christina (Tekmeria, 2016)
The epigraphic display carved on the north wall of the stage building of Aphrodisias’ theatre in the 3rd century CE, commonly referred to as the “archive wall”, is usually assumed to have been designed based on the chronology of the documents it includes. This paper argues instead in favor of a centripetal design, which placed in the center of the composition the most important documents in terms of their honorific value for Aphrodisias and its citizens. It is argued, here, that form and content, as expressed in the documents’ rhetoric, and the concrete privileges which the documents attested to, were more important than chronology to the designers of this dossier.Further, it is argued that there were two epigraphic phases, with the original phase most likely dating from 224 CE and including all documents carved above the orthostate course, and a later phase dating from 243 CE or slightly later, in which the inscriptions were extended to the orthostate course. Finally, it is suggested that the earliest letter of the dossier (document 4), may have been a letter by Cornelius Sulla.